Preparation of aldehyde substituted phthalocyanines with improved yield and their use for Schiff base metal complex formation - Sen, Pinar; Yildiz, S. Zeki; Tuna, Murat; Canlica, Mevlude (ELSEVIER SCIENCE SA, 2014)
The context of this study is based on the synthesis of tetrakis[salicyoxy-salicyhydrazone] phthalocyaninato zinc(II) (4), with four salicylhydrazone ligating groups that are directly linked through oxygen bridges to the macrocyclic core, and its tri-nuclear Zn(II) Schiff base complex Bis[bis(salicyoxysalicyhydrazone) zinc(II)] phthalocyaninato zinc(II) (5) starting from tetrakis(2-formylphenoxy) phthalocyaninato zinc(II) (3) which was obtained with an improved yield via de-protection of tetra acetalsubstituted phthalocyanine tetrakis[2-(1,3-dioxolan-2-yl) phenoxy] phthalocyaninato] zinc(II) (2) in acetic acid/FeCl3 system. The substituted zinc phthalocyanine (2) was prepared by the tetramerization of 4-[2-(1,3-dioxolan-2-yl) phenoxy] phthalonitrile (1) in the presence of the related metal salts. Complexion on the periphery to obtain trinuclear complex (5) has been performed through the reaction of the Schiff base substituted phthalocyanine (4) with the related zinc (II) salt in basic conditions in DMF. FT-IR, H-1 NMR, C-13 NMR, UV-Vis, ICP-OES and MS spectra were applied to characterize the prepared compounds. The fluorescence properties and quantum yields of the prepared complexes were investigated. The aggregation properties of the target phthalocyanines were also examined. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Reactive phtalocyanine; Schiff base; Salicylhydrazone metal complex; Synthesis; Fluorescence property; METALLOPHTHALOCYANINES; ELECTROCHEMISTRY; ORGANIZATION; DERIVATIVES; COPPER(II); PORPHYRINS; TRANSITION; ZN(II); CU(II); Chemistry